Ethers as Oxygen Donor and Carbon Source in Non‐hydrolytic Sol–Gel: One‐Pot, Atom‐Economic Synthesis of Mesoporous TiO2–Carbon Nanocomposites. Issue 19 (1st March 2018) - Escamilla‐Pérez, Angel Manuel; Louvain, Nicolas; Boury, Bruno; Brun, Nicolas; Mutin, P. Hubert
Abstract: Mesoporous TiO2 –carbon nanocomposites were synthesized using an original non‐hydrolytic sol–gel (NHSG) route, based on the reaction of simple ethers (diisopropyl ether or tetrahydrofuran) with titanium tetrachloride. In this atom‐economic, solvent‐free process, the ether acts not only as an oxygen donor but also as the sole carbon source. Increasing the reaction temperature to 180 °C leads to the decomposition of the alkyl chloride by‐product and to the formation of hydrocarbon polymers, which are converted to carbon by pyrolysis under argon. The carbon–TiO2 nanocomposites and their TiO2 counterparts (obtained by calcination) were characterized by nitrogen physisorption, XRD, solid state 13 C NMR and Raman spectroscopies, SEM, and TEM. The nanocomposites are mesoporous with surface areas of up to 75 m 2 g −1 and pore sizes around 10 nm. They are composed of aggregated anatase nanocrystals coated by an amorphous carbon film. Playing on the nature of the ether and on the reaction temperature allows control over the carbon content in the nanocomposites. The nature of the ether also influences the size of the TiO2 crystallites and the morphology of the nanocomposite. To further characterize the carbon coating, the behavior of the carbon‐TiO2 nanocomposites and bare TiO2 samples toward lithium insertion–deinsertion was investigated in half‐cells. This simple NHSG approach should provide a general method for the synthesis of a wide range of carbon–metal oxide nanocomposites. Abstract : Mesoporous TiO2 /C nanocomposites were synthesized by a one‐pot, solvent‐free, non‐hydrolytic sol–gel route based on the use of an ether as oxygen donor and carbon source.